KOMPARASI HASIL BELAJAR SISWA KELAS X MAN 2 BANYUWANGI DALAM PEMBELAJARAN MATERI AKIDAH AKHLAK MENGGUNAKAN METODE PEMBELAJARAN MAKE A MATCH DAN PICTURE AND PICTURE - Mashuri, Imam; Faishol, Riza; Rofiq, Ainur; Julian, Andi (INCARE, International Journal of Educational Resources, 2021)
This study aims to develop animation-based learning media using sparkol videoscribe on fiqh subjects in MTs Al-Kautsar Sumbersari Srono Banyuwangi. This study uses Research and Development (R&D) research with reference to the Borg & Gall research model. The subject of this trial is a material expert 1 person and a media expert learning 1 person, all validation subjects are lecturers of Islamic Religious Education study program IAI Ibrahimy Genteng Banyuwangi. In this study, the researcher describes the comparison between the learning outcomes of class X students who have been involved in two different learning methods, namely Make A Match and Picture and Picture at Madrasah Aliyah Negeri 2 Banyuwangi, located in Genteng District. Then to find out which one is superior between student learning outcomes and learning using the Make A Match or Picture and Picture method. This research is a descriptive quantitative research. With a population of class X students totaling 445 students. Meanwhile, the sample in this study were 38 children belonging to class X religion 1. The main data in this study were obtained based on the test instruments given by the researcher to the sample students. In addition, researchers also use other research instruments in the form of interviews and observations as additional data. Student learning outcomes data obtained from tests conducted by researchers are then tested for validity (validity) and reliability (reliability) to determine whether the data obtained by researchers can be analyzed further. After being declared valid and reliable. Homogeneity and normality tests were carried out to determine whether the data had a normal distribution and had the same or homogeneous data variance. Furthermore, to determine the existence of a comparison between student learning outcomes between the application of the Make A Match method with Picture and Picture, a hypothesis test was conducted in the form of a t test (t-test). The results of this study indicate that there is an influence between the methods in the paired sample t test which shows the t value of both methods on learning outcomes which is higher than the t table value. The t test results show that the t value of post-learning student learning outcomes using the Make A Match method is -29,436 while for post-learning student learning outcomes using the Picture and Picture method is -36,381. Then from this study it can also be concluded that the value of student learning outcomes influenced by the Picture and Picture method is higher than student learning outcomes that are influenced by the Make A Match method (-36.381> -29436). Thus it is concluded that in this study the alternative hypothesis (Ha) is accepted while the null hypothesis (H0) is rejected.